The Novella of I. S. Shmelev “The Man from the Restaurant”: the Genesis of the Intention (Филологический класс, 2021)
The work of V. A. Sollogub “Salalak Leisures” (1855) has not been republished until now and has not become the subject of genre analysis. In the course of the study, the authors of the article (based on the genre concept of N. L. Leiderman) prove that “Salalak Leisures” is a cycle, the connecting elements of which are the unity of themes and problems; the predominance of personal subjective forms of expression of the author’s position (including the presence of a cycle of the personal narrator common for most essays – the “Tiflis feuilletonist”); special architectonics and spatio-temporal organization (including the chronotope of the road, motives of testing and meeting), aimed at revealing the world of Caucasian nature and population; associative “braces” (images, motives, symbols, intertextual and supertext references) that support the inner unity of the cycle and deepen its problems; various shades of intonation, through which the diversity of the Caucasian flora and fauna and ethnic groups and their traditions are expressed, as well as a single emotional space of the work is created. Consideration of “Salalak Leisures” in the context of the cycle formation of the 1850s allows the authors to conclude that the work of V. A. Sollogub is an epic cycle (the term of Yu. V. Lebedev), for which (due to the merger of the novelistic and essay cycle-forming traditions of the two previous decades) is characterized by a multifaceted image of one theme, an equivalent accentuation of spatial and temporal specificity, incompleteness, “compositional looseness”, actualization of associative thinking, and heterogeneity of the genre composition of the cycle, associated, in particular, with the process of novelization. In the conclusion, the regularity of V. A. Sollogub’s appeal to the epic cycle (both in the context of the genre processes of the middle of the 19th century and in the aspect of the writer’s artistic search) is substantiated and the dynamics of narrative genres in V. A. Sollogub’s work is noted: “Salalak Leisures” suggest the writer’s movement towards a large genre form – the novel “Over the Edge” (1885), the creation of which was largely prepared by the evolution of the central Sollogub character – “a kind, but weakwilled good old sport”.